Loss of Neuroprotective Factors in Neurodegenerative Dementias: The End or the Starting Point? - Benussi, Luisa; Binetti, Giuliano; Ghidoni, Roberta (Frontiers in Neuroscience, 2017)
Recent clinical, genetic and biochemical experimental evidences highlight the existence of common molecular pathways underlying neurodegenerative diseases. In this review, we will explore a key common pathological mechanism, i.e. the loss of neuroprotective factors, across the three major neurodegenerative diseases leading to dementia: Alzheimer’s disease (AD), Frontotemporal dementia (FTD) and Lewy body dementia (LBD). We will report evidences that the Brain Derived Neurotrophic Factor (BDNF), the most investigated and characterized brain neurotrophin, progranulin, a multi-functional adipokine with trophic and growth factor properties, and cystatin C, a neuroprotective growth factor, are reduced in AD, FTD and LBD. Moreover, we will review the molecular mechanism underlying the loss of neuroprotective factors in neurodegenerative diseases leading to dementia, with a special focus on endo-lysosomal pathway and intercellular communication mediated by extracellular vesicles. Exploring the shared commonality of disease mechanisms is of pivotal importance to identify novel potential therapeutic targets and to develop treatments to delay, slow or block disease progression.